Human-bat interactions in central Colombia: Regional perceptions of a worldwide fragile life zone - Ramírez Fráncel, Leidy Azucena; García-Herrera, Leidy Viviana; Guevara, Giovany; Losada-Prado, Sergio; K. Lim, Burton; Villa-Navarro, Francisco Antonio; Reinoso-Flórez, Gladys (Ethnobiology and Conservation, 2021)
The study of human relationships with other components of the landscape allows us to understand the dynamics of ecological communities and biodiversity. Although there has been an increase in ethnobiological studies, little is known about the interaction between humans and bats. The objective of this study was to evaluate the perceptions and attitudes about bats by people in the fragile life zone of the tropical dry forest of Colombia. We selected four representative areas and evaluated three different aspects: (1) biological and ecological knowledge, (2) uses and cultural beliefs, and (3) interactions between humans and bats. The data were collected through surveys of 18 questions to 197 people with a gender ratio close to parity. The data obtained are presented as descriptive statistics by using a generalized linear model (GLM). The results showed that people’s knowledge and attitude towards bats depend on the covariates of education and gender of the respondents. Women (t= 3.76; P=0.004) and people with a higher education level (t=3.65; P<0.004) had positive attitudes towards bats. Although the ecosystem services provided by bats were clearly recognized, the need for conservation were not as obvious. These results indicate that human-bat relationships are complex and may be the result of multiple social and cultural factors. Likewise, these cross-cultural perceptions must be understood and addressed in the development of actions that promote the conservation of bats in tropical forests.